Implementasi Nilai Keadilan Dalam Pancasila Guna Membangun Karakter Dan Etika Pendidik Di Perguruan Tinggi - Siska Marlina Siska Marlina (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2022)
Based on the basic values ​​in the law presented by Magnis-Suseno by quoting German scholars, among others, Reinhold Zippelius, states that there are three basic values ​​that must be realized in the law namely: the value of equality, freedom, and solidarity. The values ​​contained in Pancasila itself are Religious Value, Family Value, Tolerance Value, Gotong Royong Value, and Value of Justice. In this case, we as the authors examine the issues of educators who characterized it in terms of the value of Justice in Pancasila which includes: Justice; in equilibrium, in equality or non-discrimination, in the granting of rights to the parties entitled, and on the basis of their degree and feasibility. Pancasila as the basis and ideology of the state is a political agreement of the founding fathers when the country of Indonesia was founded.